Nauczanie kultury poprzez technologie teleinformatyczne w ponowoczesnym świecie – (nie)wykorzystane możliwości nowych technologii - Sikorska, Joanna (Studia Edukacyjne, 2020)
Teaching culture of foreign countries was until recently done by traditional means i.e. movies, letters sent by post to schools in other countries or by means of a textbook. Now, when schools are getting more computerized, certain elements of teaching have been revolutionized. They include, for example, culture teaching, which received a new meaning through the use of eTwinning. Because of it, teachers and students can communicate much easier through the platform, Facebook or by e-mail with other schools from the EU that are in this program. They can take part in projects with other schools and learn the cultural differences between their countries together. In this article I try to point out the challenges which multicultural ICT use can bring to education.